Evaluasi Kesesuaian Lahan Tanaman Perkebunan di Kecamatan Selo Kabupaten Boyolali - Ristriana, Amanda Indrati; Budiyanto, Susilo; Purbayanti, Endang Dwi (Politeknik Negeri Lampung, 2023)
Selo District has great potential for developing plantation crops; however, the amount of production still needs to grow. The purpose of this study is to determine the soil suitability class of plantation crops (arabica coffee, tobacco, cloves, cocoa, and tea), identify limiting factors in the study area, and suggest ways to overcome them to increase land suitability classes. The study was conducted in Selo District, Boyolali Regency from November 2022 - December 2022, and the Plant Ecology Laboratory, Faculty of Animal Husbandry and Agriculture, Diponegoro University. This study used an investigative method consisting of multiple stages, laboratory data analysis, and data processing. As a result, Selo District has actual land suitability N (not suitable) for Arabica coffee and Cocoa in all area tests. In contrast, tobacco, clove, and tea had suitability classes S3 (marginally appropriate) to N (not suitable). The limiting factors that dominate are air humidity, pH, C-organic, soil texture, and slope. Efforts can be made to improve the limiting factors in the area by adding fertiliser and organic matter, feeding dolomite, and making mounds. These improvement efforts aim to increase the land suitability class for plantation crops.